Synergy between Philosophy of Education and Technology: Toward a More Innovative Approach to Learning - Dian, Dian; Fauziyyah, Salma; Arpiandi, Zoeji; Utari, Nistia Sri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
In the era of globalization and rapid technological advancement, innovation in education is crucial. As one of the key pillars of human and societal development, education must continuously evolve to address the needs and challenges of modern times. Preparing the younger generation for future challenges necessitates prioritizing educational innovation on the global policy agenda. The philosophical foundation of education is essential in providing a framework for understanding the purpose of education, teaching methods, and the relationship between education, individuals, and society. This research aims to serve as a reference for educators, curriculum developers, and policymakers in designing effective and relevant learning strategies and to contribute to the academic literature on the intersection of education and technology. The study adopts a mixed-methods approach, combining both qualitative and quantitative techniques. The research begins with a qualitative phase, where in-depth interviews and literature analysis are used to explore integrating educational philosophy with technological advancements in learning. This qualitative step identifies key challenges, opportunities, and needs within current educational systems. In the subsequent quantitative phase, surveys and questionnaires are distributed to a larger sample of educators and students to gather data on their experiences and perceptions regarding the use of technology in education. The study results confirm that a deep integration of educational philosophy with advancements in learning technology is crucial for creating a holistic and effective education system. This approach fosters character development, enhances critical thinking skills, and prepares learners to face future challenges with empathy, critical thinking, and wisdom. The data collected through qualitative and quantitative methods reveal significant correlations between educational philosophy's application and technology's successful integration in fostering an adaptable, forward-thinking educational environment.